The Effects of Stress Management Training on Communication Skills and Attribution Beliefs on Women with Adjustment Disorders - Safinia , Gooya; Ebrahimi Moghadam , Hossein; Abolmaali, Khadijeh (Shahroud Journal of Medical Sciences, 2021)
Background: Recognizing the effective factors in marital relationships, control and manage them are among the crucial methods in solving marital problems and achieving marital satisfaction. The present study aimed to investigate the effects of stress management training on communication skills and attribution beliefs on women with adjustment disorders.Methods: The research method was quasi-experimental with a pre-test, post-test, and follow-up design and a control group. The statistical population included all women with adjustment disorders who were referred to the psychological clinics of district 1 of Tehran in 2020. Thirty women who were willing to participate in the study were selected as the sample using convenience sampling and randomly divided into experimental and control groups (n=15 per group). The experimental group underwent eight sessions (90 minutes sessions per week) of stress management training. The follow-up was performed after 60 days. The research instruments included the Dyadic Adjustment Scale (DAS), the Relationship Attribution Measure (RAM), and the Jarabak Communication Skills Questionnaire (JCSQ). Data analysis was conducted using repeated-measures ANOVA.Results: The results indicated that stress management training improved communication skills and attribution beliefs in women with adjustment disorders (Pvalue=0.0001).Conclusions: Stress management training can be recommended as an intervention program to improve the quality of life of women with adjustment disorders.Keywords: Stress management, Communication, Attribution, Beliefs, Adjustment, Women